2007
DOI: 10.1590/s0102-05362007000300026
|View full text |Cite
|
Sign up to set email alerts
|

Épocas de plantio e doses de silício no rendimento de alface tipo americana

Abstract: A alface é a hortaliça folhosa mais consumida no país (Santos et al., 2001), sendo que a alface tipo americana vem adquirindo importância crescente. O plantio deste tipo de alface visa atender as redes de "fast foods" e, atualmente, tem-se constatado o aumento no consumo desta hortaliça também na forma de salada.A época de plantio é fator fundamental no cultivo, por tratar-se de cultura bastante influenciada por condições ambientais. Temperaturas acima de 20ºC estimulam o pendoamento que é acelerado à medida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 8 publications
(1 reference statement)
2
7
0
7
Order By: Relevance
“…Similar results were found by Resende et al (2007) who observed positive responses with Si spraying in crisphead lettuce, where an increase in commercial and total values on fresh matter was found. The silicon application on different varieties of plants has shown to improve the productivity and quality of vegetable because it provides nutrients to the vegetables, greater turgidity to the leaves, due to less water loss by the plant, since this nutrient tends to accumulate in the leaf epidermis serving as a barrier to water loss through transpiration by the plant (Barker and Pilbeam, 2007).…”
Section: Resultssupporting
confidence: 88%
“…Similar results were found by Resende et al (2007) who observed positive responses with Si spraying in crisphead lettuce, where an increase in commercial and total values on fresh matter was found. The silicon application on different varieties of plants has shown to improve the productivity and quality of vegetable because it provides nutrients to the vegetables, greater turgidity to the leaves, due to less water loss by the plant, since this nutrient tends to accumulate in the leaf epidermis serving as a barrier to water loss through transpiration by the plant (Barker and Pilbeam, 2007).…”
Section: Resultssupporting
confidence: 88%
“…Esse destaque se deve, principalmente, às características apresentadas por este grupo, que se diferencia dos demais por apresentar folhas externas de coloração verde-escura, folhas internas de coloração amarela ou branca, imbricadas, semelhantes ao repolho e crocantes, além de apresentar maior duração pós-colheita, possibilitando o transporte a longas distâncias principalmente, as redes de fast foods (Yuri et al, 2002a). Tem-se constatado maior demanda dessa alface e aceitação pelo mercado consumidor brasileiro, na forma de salada (Resende et al, 2007;Sala & Costa, 2012). Nos Estados Unidos, esse grupo de alface denominado crisphead lettuce, é considerado o mais importante dentre as hortaliças para ser consumido em forma de saladas cruas, tendo um consumo per capita superior a 11,3 kg/ano (Sanders, 2016).…”
Section: Grower's Pageunclassified
“…Despite the proven effects of Si on the mentioned metabolic processes, little information on its effects on traits related to post-harvest quality can be found. Resende et al (2007) showed that foliar application of Si reduced oxidation in the outer leaves of lettuce, causing the formation of compact "heads", with a higher retention of the green coloration, compared to the control (without Si). Concerning tomato, Stamatakis et al (2003a) observed an increase in concentration of soluble solids, vitamin C, lycopene and fruit firmness by adding Si to the nutrient solution.…”
Section: Palavras-chavementioning
confidence: 99%